High-technology employment: a NAICS-based update. - Hecker, Daniel E. (Monthly Labor Review, 2005)
Among high-technology industries--those with a high proportion of scientists, engineers, and technicians--some are projected to grow rapidly; overall, however, this group of industries is expected to continue to grow slowly